The missing link in the relationship of corporate social responsibility and firm value in Indonesia - Istianingsih, Istianingsih (Library of Sultan Agung Islamic University, 2022)
The inconsistency of research results on the relationship between Corporate Social The inconsistency of research results on the relationship between Corporate Social Responsibility and Firm Value indicates missing variables in the relationship. This study aims to test Profitability as a moderator and mediator that bridges CSR and Firm Value's relationship. his type of research is causal-comparative research. The population in this study includes companies manufacturing listed on the Indonesia Stock Exchange (IDX). Selection of the sample with the purposive sampling method. This research's total sample is 107 companies for three periods, so the total sample size is 107 companies x 3 periods 321 data. The analysis used is path analysis and test Moderated Regression Analysis (MRA). The results showed that CSR positive and significant effect on Profitability. On the other hand, CSR is a significantly negative effect on firm value. As measured by return on assets (ROA), Profitability has a significantly positive effect on firm value. CSR positive and significant effect on the firm value of the Company through Profitability. On the other hand, as measured by return on assets (ROA), Profitability proved unable to moderate the relationship between CSR with the firm's value.